Immunotherapy as a neoadjuvant preoperative treatment for locally advanced pulmonary sarcomatoid carcinoma: a case report of clinical efficacy - Hanhan Li; Hanhan Li; Ruilian Chen; Wei Guo; Shang Xiang; Shang Xiang; Jiayang Huang; Jiayang Huang; Hanrui Chen (Frontiers in Oncology)
BackgroundPulmonary sarcomatoid carcinoma (PSC) is a rare subtype of non-small cell lung cancer (NSCLC) with a generally poor prognosis. Studies have shown that the survival rate for advanced-stage patients is less than 5%, with a median overall survival (OS) of less than 6.5 months.Case reportHerein, we report a case of locally advanced PSC in a 56-year-old male patient who received platinum-based double-drug therapy combined with anti-angiogenic drugs, followed by immunotherapy as the first-line systemic treatment. After undergoing eight cycles of neoadjuvant therapy, the opportunity for surgery arose. Postoperative pathology confirmed that the neoadjuvant chemotherapy in this regimen achieved pathological complete remission (pCR). At present, the patient maintains a good quality of life, continues with immunotherapy for consolidation and prevention of recurrence, and has reached a survival period of 10 months.ConclusionFor patients with locally advanced PSC who do not have significant genetic mutations, the use of immunotherapy as a first-line neoadjuvant and adjuvant therapy may hold promise for achieving a pCR. Further research into this treatment protocol is warranted.